La crisis en la educación. Un recorrido por el pensamiento de Hannah Arendt - Hours, Germán; Boulan, Noralí (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
Hannah Arendt is mainly known as a political essayist, although education hasn´t been a major subject in her work, she focused on it with special attention. In "Between past and future" (1954), Arendt postes a chapter to "Crisis in education", being this the one and only manuscript exclusively dedicated to this theme. In this essay, she makes a point out of the crisis in the american educational system during 1950’s, as well as the crisis in the western education, which no doubt, gives arguments to think over the contemporary education status and the school institutions in Latin America. The importance, therefore, to resume Arendt to analyze the tension in the actual educational field, is that her vision has transferred time and space boundaries, to be considered extremely relevant in the present potential political analysis.